2019
DOI: 10.1371/journal.pcbi.1006650
|View full text |Cite
|
Sign up to set email alerts
|

BEAST 2.5: An advanced software platform for Bayesian evolutionary analysis

Abstract: Elaboration of Bayesian phylogenetic inference methods has continued at pace in recent years with major new advances in nearly all aspects of the joint modelling of evolutionary data. It is increasingly appreciated that some evolutionary questions can only be adequately answered by combining evidence from multiple independent sources of data, including genome sequences, sampling dates, phenotypic data, radiocarbon dates, fossil occurrences, and biogeographic range information among others. Including all releva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
2,630
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,173 publications
(2,907 citation statements)
references
References 116 publications
13
2,630
0
8
Order By: Relevance
“…This is also what we observed on the ancestry recombination graph reconstructed using sequences of the 85 European STs and generated in beasT2 (Bouckaert et al, 2019;Figure 5 Ixodes ricinus is a generalist tick and birds are known to be important hosts for its immature stages (Norte et al, 2012;Santos-Silva et al, 2011). The other tick species (I. frontalis, I. arboricola and I. ventalloi) and genera (Haemaphysalis and Hyalomma) collected from birds in this study have also been previously reported on birds (Diakou et al, 2016;Norte et al, 2012;Pérez-Eid, 2007) and differ in vector competence for Borrelia (Eisen & Lane, 2002;.…”
Section: Multilocus Sequence Typing/multilocus Sequence Analysis (Msupporting
confidence: 83%
“…This is also what we observed on the ancestry recombination graph reconstructed using sequences of the 85 European STs and generated in beasT2 (Bouckaert et al, 2019;Figure 5 Ixodes ricinus is a generalist tick and birds are known to be important hosts for its immature stages (Norte et al, 2012;Santos-Silva et al, 2011). The other tick species (I. frontalis, I. arboricola and I. ventalloi) and genera (Haemaphysalis and Hyalomma) collected from birds in this study have also been previously reported on birds (Diakou et al, 2016;Norte et al, 2012;Pérez-Eid, 2007) and differ in vector competence for Borrelia (Eisen & Lane, 2002;.…”
Section: Multilocus Sequence Typing/multilocus Sequence Analysis (Msupporting
confidence: 83%
“…Both for generating accurate predictions of epidemic risk and controlling the outbreak, it is vital to begin contact tracing before numerous transmission chains become widely distributed across space [38,39] Second, viral genome sequences provide information on both the timing of the outbreak [40][41][42] and structure of secondary cases [43][44][45]. For example, methods exist to reconstruct transmission trees for sampled sequences using simple mutational models to construct a likelihood for a specific transmission tree [46,47] and translate coalescent rates into key epidemiological parameters [48][49][50]. Despite the potential for genome sequencing to revolutionize outbreak response, the global public health community still struggles to coordinate data sharing across international borders, between academic researchers, and with private companies [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The most well-known BI software includes mrbayes (Ronquist et al, 2012b), exabayes (Aberer et al, 2014), phylobayes (Lartillot et al, 2013), revbayes , beast (Suchard et al, 2018), and beast2 (Bouckaert et al, 2019). mrbayes is a well-established program, with very helpful documentation and many online tutorials available.…”
Section: Concatenation-based Analysesmentioning
confidence: 99%